Evolutionary medicine - Nesse, Randolph (Henry Stewart Talks, 2023)
What is evolutionary medicine, Explaining traits, Natural selection and disease vulnerability, Cancer and natural protection, Adaptation and maladaptation, Wrenching transitions, Defenses vs. defects, The future of evolutionary medicine